Мягкий характер - Гераскина Лия Борисовна (Школьная библиотека, 2019)
Экземпляры: (20220218) / Инвентарный номер: 42013 / Цена: 95.00 / Сис.шифр: 84(2=411.2)6 / Авт.знак: Г 37 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6